Feeding guanidinoacetic acid to broiler chickens can compensate for low dietary metabolisable energy formulation. Issue 3 (4th May 2022) - Pirgozliev, V.; Rose, S. P.; Mirza, M. W.; Whiting, I. M.; Malins, H.; Bauer, L.; Lemme, A.
ABSTRACT: 1. This study compared the responses of broilers to diets supplemented with the same level of guanidinoacetic acid (GAA) but formulated to have different N-corrected apparent metabolisable energy (AMEn) contents. The study involved 1280, one-day-old Ross 308 broilers, in 64 pens comprising 32 pens of males and 32 pens females, (20 birds in each) aged from 0 to 42 d. 2. Commercial AME levels of 12.55 MJ/kg, 12.97 MJ/kg and 13.18 MJ/kg in the starter, grower and finisher diets, respectively, were set for the positive control (PC) feed. Four dietary treatments were prepared: PC (as above); negative control 1 (NC; PC – 0.21 MJ ME /kg); NC1 + 0.06% GAA; NC2 (PC – 0.42 MJ ME/kg + 0.06% GAA). Each diet was provided in 16 pens (eight male and eight female), following randomisation. 3. Overall, birds fed NC1 had lower feed intakes (FI) compared to birds fed the PC and NC2+ GAA, lower weight gain (WG) compared to all the other diets and lower final body weight than birds fed the GAA diets (P < 0.05). There was a diet x sex interaction (P = 0.039), whereby feeding NC+GAA to female birds improved feed efficiency compared to being fed NC2 and NC1+ GAA, but not in males. Birds fed diets with GAA had a higher poultry efficiency factor (P < 0.001) than those fed NC1. 4. There were no effects of treatment or sex on litter moisture, footpad score, white striping, wooden breast, AMEn, dry matter and fat retention (P > 0.05). However, the diet NC1+ GAA had 11.2% higher nitrogen retention coefficient compared to the NC1 diet (P = 0.038). 5. Overall, the results implied that lower performance induced by a reduction of dietary AMEn in the range of 0.21 to 0.42 MJ/kg was more than compensated by supplementing 600 g/t GAA to the feed.